The knowledge, attitudes, and perceptions toward the Oxford AstraZeneca COVID-19 vaccine amongst Primary Health care workers in North-Central Trinidad - Khan, Raveed; Albert, Rachel; Awe, Leann; De Four, Renee; Francois, Tichad; Hinds, Tahirah; Kellman, Avery; Maharaj, Kelsey; Mahon, Renea; Pierre, Chanel; Ramai, Alana; Baksh, Rameez (Frontiers in Public Health, 2023)
Aim: To determine the effects of knowledge, attitudes, and perceptions of primary care health workers towards receiving the Oxford AstraZeneca vaccine in North Central, Trinidad. Methods: A pretested de novo questionnaire containing forty-eight (48) closed ended questions and one (1) open ended question was used to gather data. Descriptive and inferential statistics were used to analyze the data obtained from the questionnaire. These included percentages, means and standard deviations for the descriptive aspect and the Chi-Square test to examine any significant associations. Analysis of Variance (ANOVA) was used to assess any significant differences in means among several categories and the independent samples t-test for assessing any significant difference in means between two categories. Results: 273 respondents completed the questionnaire. Most of the participants (72.2%) were female and within the age range 25-36 (56.0%). The mean knowledge score about the AstraZeneca vaccine was 16.28 (SD = 2.28) out of 19 with an overall correct response rate of 79%. 30.4 % of participants had a good attitude score and 59.7% had a positive perception towards the AstraZeneca vaccine. There were significant associations between Knowledge and Marital status (p = 0.001), Income level (p = 0.001), Education level (p < 0.001), and Length of employment (p = 0.041); Attitudes and sex (p = 0.01), age (p = 0.04), marital status (p = 0.009), income level (p < 0.001), Education level (p = 0.005) and category of staff (p <0.001); Perception and sex (p = 0.002), marital status (p = 0.027), income level (p < 0.001) and category of staff (p <0.001). Conclusions: The main contributors to vaccine hesitancy were inadequate duration of clinical trials and fear of adverse side effects. A significant number of participants (17%) were unwilling to get the vaccine due to lack of information.